Development and implementation of a high nature value (HNV) farming indicator for Denmark. (February 2016) - Brunbjerg, Ane Kirstine; Bladt, Jesper; Brink, Martin; Fredshavn, Jesper; Mikkelsen, Peter; Moeslund, Jesper E.; Nygaard, Bettina; Skov, Flemming; Ejrnæs, Rasmus
Highlights: We developed a national fine resolution HNV farming map for prioritization of HNV-subsidies. Land cover, farming system and species occurrence constituted the final HNV farming indicator. The fine-resolution national HNV farming indicator documented is ready for implementation. Abstract: During the latest decades, conservation awareness have increased and conservation of biodiversity is no longer an agenda restricted to pristine natural areas of high value but is being integrated in cultivated landscapes characterized by increasing fragmentation and anthropogenic pressures. Conservation of species has become relevant even in agricultural areas especially in countries heavily influenced by intensive farming and ubiquitous infrastructure. Based on the UN biodiversity convention all EU membership countries are obliged to develop a high nature value (HNV) farming indicator. The purpose of such an indicator is to provide a basis for informed decisions in prioritizing agricultural subsidies allocating these to high nature value areas. Here, the development of a national HNV farming indicator for Denmark is presented and its application in the Danish government-controlled agricultural subsidy system is outlined. The Danish HNV farming indicator is based on landscape structural parameters, known occurrences of natural and semi-natural habitats, current land use and the distributions of rare and threatened species. It covers all agricultural areas as well as Natura 2000 areas and nationally protected sites in Denmark, ranking them on a 0–13 point scale from low to high nature value according to their estimated value for threatened and rare biodiversity. The Danish government recognizes areas reaching at least 5 points as HNV farming areas eligible to subsidy and from 2015 and onwards the HNV farming indicator will be implemented for allocating part of the agricultural subsidies under the Rural Development Program in Denmark. The indicator will be updated annually to include the growing knowledge of species occurrence and land use changes.